A Cautiously Pessimistic Appraisal of Trends in Toxics Regulation - David E. Adelman (Washington University Journal of Law & Policy, 2010)
This Article will draw on the one-hundred year history of drug regulation, which represents the most stringent regulatory system for chemicals of any kind. An examination of this broader experience exposes several commonalities and tradeoffs inherent in chemical regulation. It also offers a comparative perspective on the strategies used in the regulation of chemicals that suggests an upper limit for the stringency of regulation that is politically and scientifically viable. Two important insights emerge from this comparative analysis: (1) the ex ante-ex post dichotomy that is often drawn between common law and statutory law is overstated—if not simply false—for chemical regulation, and (2) for most chemicals tiered "precautionary" systems like those embodied in the Registration, Evaluation, and Authorization of Chemicals program ("REACH") represent more of a change in rhetoric than a fundamental shift in substance over the status quo. Complementing the comparative historical analysis, this Article will provide an overview of recent scientific developments and their implications for toxics regulation. I expect the direct impacts to be marginal, at least for the foreseeable future. More importantly, given the limited resources available to toxics programs and the steep opportunity costs that these financial constraints impose, I will advocate that the Environmental Protection Agency ("EPA") and National Institute for Environmental Health Sciences ("NIEHS") invest modestly in toxicogenomic research. The emerging complexity of human genetics suggests that it would be prudent to allow research to progress in the biomedical sciences before focusing more intensely on toxicogenomics. The final part of the Article examines promising opportunities to improve the regulation of toxic substances, which is the subject of renewed interest in Congress and rising support from a broad cross-section of stakeholders. It will evaluate three primary policies: the virtues of tiered regulatory regimes, the potential role of post-marketing testing, and the value of complementary innovation-oriented policies to promote development of "green chemistry" processes and compounds. Each will be discussed with an eye toward emerging legislative efforts to amend TSCA.
Keywords: Hazardous substances; Toxicogenomics; United States. Environmental Protection Agency; Toxic Substances Control Act